Retinal microvascular alterations in patients with active rheumatoid arthritis without cardiovascular risk factors: the potential effects of T cell co-stimulation blockade - Piantoni, Silvia; Regola, Francesca; Angeli, Fabrizio; Caproli, Alessia; Trovati, Annalisa; Tomasi, Cesare; Chiarini, Giulia; Rossini, Claudia; Rosei, Claudia Agabiti; De Ciuceis, Carolina; Franceschini, Franco; Muiesan, Maria Lorenza; et al. (Frontiers in Medicine, 2024)
Background The evaluation of microvascular alterations might provide clinically useful information for patients with an increased cardiovascular (CV) risk, such as those with rheumatoid arthritis (RA), being the small artery remodeling the earliest form of target organ damage in primary CV diseases, such as arterial hypertension. The evaluation of retinal arterioles is a non-invasive technique aimed to identify an early microvascular damage, represented by the increase of the wall-to-lumen ratio (WLR) index. Abatacept (ABA), a T-cell co-stimulator blocker, is used to treat RA. A CV protective action was hypothesized for its peculiar mechanism of action in the modulation of T-cells, potentially involved in the pathogenesis of CV comorbidity. The study aimed to non-invasively investigate morphological characteristics of retinal arterioles in a cohort of RA patients treated with ABA. Materials and methods Seventeen RA patients [median (25th-75thpercentile) age = 58 (48–64) years, baseline 28-joint Disease Activity Score DAS28-C-reactive protein (DAS28-CRP) = 4.4 (3.9–4.6), body mass index (BMI) = 24.2 (23.4–26) kg/m2, rheumatoid factor positive:52.9%, anti-citrullinated peptide autoantibodies positive:76.5%] without known CV risk factors (arterial hypertension, diabetes, hypercholesterolemia, previous CV events, smoking) were evaluated by the adaptive optics imaging system of retinal arterioles before and every 6 months of therapy with ABA (T0, T6 and T12). Office blood pressure evaluation, 24-h ambulatory blood pressure monitoring and tissue-doppler echocardiography were also performed. Results A progressive significant reduction of the WLR of retinal arterioles was observed [T0 = 0.28 (0.25–0.30), T6 = 0.27 (0.24–0.31), T12 = 0.23 (0.23–0.26); p T0 vs. T6 = 0.414; p T6 vs. T12 = 0.02; p T0 vs. T12 = 0.009], without significant variations in other parameters. The T0-T12 reduction of WLR was correlated with that of DAS28-CRP (r:0.789; p = 0.005). Moreover, a significant reduction of diastolic office blood pressure and a trend for reduction of daily pressure measured by ambulatory monitoring were observed. Conclusion In a cohort of RA patients without known CV risk factors, a reduction of retinal microvascular alterations was demonstrated after treatment for 12 months with ABA, in parallel with the reduction of disease activity. These results might suggest the possibility of microvascular abnormalities regression induced by the immune system modulation.